2015
DOI: 10.1088/0741-3335/57/12/125011
|View full text |Cite
|
Sign up to set email alerts
|

Study of near scrape-off layer (SOL) temperature and density gradient lengths with Thomson scattering

Abstract: Improvements to the Thomson Scattering diagnostic have enabled the study of near scrape-off layer (SOL) decay lengths in the 2014 ASDEX Upgrade experimental campaign. A database of H-mode discharges has been studied using a two-line fit method for the core and log-linear fit for the near SOL region under both attached and detached divertor conditions. SOL electron temperature profiles have been found to have a radial exponential decay distribution and which does not vary poloidally, consistent with the two-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
96
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 29 publications
24
96
2
Order By: Relevance
“…Classical heat conduction relates ∥ and the temperature decay width, , through the well know results ∥ , . Previous study of H-mode in attached condition showed that this relation is consistent with the upstream Te and target IR data indicating a small broadening (not detectable within experimental errors) of this part of the SOL by radial transport [12]. The electron temperature, , profiles in the near SOL have been found to have a radial exponential decay distribution which, moreover does not vary poloidally.…”
Section: Introductionsupporting
confidence: 81%
“…Classical heat conduction relates ∥ and the temperature decay width, , through the well know results ∥ , . Previous study of H-mode in attached condition showed that this relation is consistent with the upstream Te and target IR data indicating a small broadening (not detectable within experimental errors) of this part of the SOL by radial transport [12]. The electron temperature, , profiles in the near SOL have been found to have a radial exponential decay distribution which, moreover does not vary poloidally.…”
Section: Introductionsupporting
confidence: 81%
“…A recent multi‐machine empirical scaling law for the H‐mode found λ q , targ ∝ Bpol1 and has predicted λ q , ITER ≈ 1 mm, raising concern for future reactor devices. Moreover, the B pol functional dependence has been retrieved in other H‐mode experiments and is observed even for the L‐mode both in limited and divertor configurations, suggesting some universality in the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 66%
“…From the divertor entrance situated at the target distance L div to the mid-plane, the narrow power width λ q is supposed to be valid, which is about 2 mm in AUG at I p = 1 MA and predicted to be slightly below 1 mm in ITER [7]. The power width λ q derived from IR measurements at the target and the validity of Spitzer conductivity could recently be confirmed by Thomson scattering measurements of the T e width in the outer midplane using the relation λ q = 2 7 λ T e [25]. At the target, a broadened power width λ int is measured due to the effect of the power spreading S, via λ int ≈ λ q + 1.64S [22].…”
Section: D Sol Model With Momentum Loss Processesmentioning
confidence: 84%